Effects of inter-individual variability in experimenters’ sensitivity and training on behavioral assessment of animal models of vestibular disorders - Boularand, Romain; Hatat, Bérénice; Bringuier, Claire; Chanut, Nicolas; El Ahmadi, Abdessadek; Besnard, Stéphane; Tighilet, Brahim; Chabbert, Christian (Frontiers in Neurology, 2025)
BackgroundThis study was designed to explore the correlation between animal behavioral assessment quality and rater’s individual sensitivity and training.MethodsWe selected different raters to form a panel to rate the severity of posturo-locomotor deficits in animals displaying excitotoxic or ototoxic lesions-induced vestibular syndrome. All raters, regardless of their scientific level, received brief training based on videos and tutorial files. They then had to score videos of rats with different types and stages of vestibular syndromes. All data were collected and analyzed.ResultsInter-individual variability in raters significantly altered the results of behavioral assessment of posturo-locomotor deficits in vestibulo-lesioned animals. Neither gender nor scientific level had an impact on the results. In contrast, the sensitivity of the individual to animal welfare impacted the mean score in the ototoxic lesion model. Raters with high sensitivity tended to exaggerate the symptomatology.ConclusionThe use of automated assessments of posturo-locomotor deficits in vestibulo-lesioned rodents, is the best solution to limit these assessment biases.